Intercultural communication between Poland and Germany within the European Union and resulting problems (Economic and Political Thought, 2016)
The article deals with the intercultural relations between Poland andGermany within the European Union. The first part of the article is devotedto the analysis of cultural similarities and differences between the societiesof the two countries. The second part of the article, on the other hand, theproper one from the point of view of its title, presents the issue of interculturalcommunication between Poland and Germany exemplified by three casestudies: Polish and German business culture, Polish and German local bordertraffic and intercultural relations between Polish and German students atEuropean University Viadrina in Frankfurt (Oder).